The use of iPads to enhance Task-Based Language Teaching - Selwyn-Álvarez, Hannah Tamara (My University, 2023)
Task-Based Language Teaching (TBLT) is a methodology that has shown promising results within Language Teaching and Learning. Technology such as the iPad is also a tool that offers promise within the educational hemisphere. As the technology of iPads are becoming more accessible within education, its effective use needs further observation. This Final Degree Essay therefore proposes a project of intervention to allow for the observation of how TBLT can be enhanced through the use of the educational technology iPads, along with motivation-related modifications to the TBLT approach, so as it can be better suited for primary students in a sixth of primary class. Motivation is a key factor in language learning, and task-based learning requiring meaningful-language use is a motivating factor in TBLT, however, for young learners, this project of intervention will make use of hypothetical elements within tasks in order to foster a more fun-based task for primary students to engage in that are based on real-world language interactions.
Keywords: Task-Based Language Teaching; iPads; motivation; EFL; Grado en Maestro en Educación Primaria